Burn Scar Reconstruction of the Neck with FTSG Obtained from Lower Abdominal Skin - Sadrollah Motamed; Ramin Jahadi; Mohsen Asadi; Hasan Motamed (Acta Medica Iranica, 2011)
Burns account for a significant proportion of injuries, and of these the face, neck, and anterior torso are commonly affected. Burn scars remain a lasting reminder of the insult both for the patient and the outside world. There is little doubt that the change in appearance and the limitation imposed by a burn scar contribute to negative body image. Treatment of hypertrophic scars in the neck has been quite challenging if there is no intact tissue for local flaps. So application of full-thickness skin grafts could be of great value. We applied full-thickness grafts obtained from lower abdominal skin for treatment of severe neck contractures in four patients when other treatment modalities such as local flaps could not be used. Full-thickness skin graft of the neck is a safe and reliable treatment option with fairly good functional and aesthetic results. It has little donor site morbidity in spite of providing a large surface area of full-thickness skin.